(untitled) (Research, Society and Development, 2021)
The gluten-free pasta (GFP) has a higher cost and is often brittle, pale, and poorly balanced in macro and micronutrients when compared to wheat-based pasta. This study aimed to use the biofortified sweet potato flour, a natural source of color and provitamin A ingredient, with rice flour, hydrolyzed soy protein concentrate, and carboxymethyl cellulose gum to produce GFP, using a central composite rotatable design with three factors (23) and the central point. The GFP were evaluated by instrumental color analysis, and visual analysis of technological characteristics (presence of cracks, defect, and shape aspect), used for selection. Three GFP were selected: E1, E2 and E12, which showed absence of breaks or defects and an intermediate aspect after cooking, which were submitted to nutritional, functional and sensory evaluations. These GFPs presented levels of β-carotene of 135.22, 292.04 and 147.54 µg/g (dry basis), respectively, and showed sensory overall liking means in the acceptance region (>4.5) with no significant differences among them. According to the penalty analysis, the parameters color and consistency penalized these averages. Therefore, optimizing the ingredients’ concentrations improved the nutritional value and the sensory acceptability of GFP.